Training of scientific generation of mathematicians - Ivanauskas, Feliksas (Lietuvos matematikos rinkinys, 2001)
The training of scientific generation of Lithuanian mathematicians is a vital objective of national significance. It is inseparable from general trends of training of scientific generation in Lithuania. This paper reviews the general dynamics of the number of scientists in all scientific fields. The scientific staff situation in mathematics, computer science and partly in mathematical educology is considered. The contribution of separate scientific and educational institutions into the training of generation is examined. General conclusions and recommendations are presented.